2021
DOI: 10.3233/jvr-201115
|View full text |Cite
|
Sign up to set email alerts
|

Differences in employment concerns between Hispanic and Caucasian persons with multiple sclerosis: A propensity score matching analysis

Abstract: BACKGROUND: Little is known about the experiences and concerns of Hispanic Americans with multiple sclerosis (MS), especially how their experiences and concerns compare to those of Caucasian Americans with MS. OBJECTIVE: The purpose of this study was to examine differences in satisfaction with the overall employment situation between two matched samples of adults with MS, namely, Hispanics and Caucasians. METHODS: Participants in this study responded to a national survey of the employment and community living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The impact of COVID-19 on job obtainment and retention has been a focus of research as of late. Significant job loss among individuals with chronic conditions and disabilities during the pandemic has been shown in recent literature [31,32], with research showing a negative impact on health and psychological wellbeing of people with disabilities due to isolation based on lack of employment [33]. Study findings showed significant direct effects of anxiety, perceived barriers to employment on work readiness of individuals with NF1 (compared to the control group), and while quality of life were significant indirect effects.…”
Section: Vocational Rehabilitation As An Interventionmentioning
confidence: 78%
See 1 more Smart Citation
“…The impact of COVID-19 on job obtainment and retention has been a focus of research as of late. Significant job loss among individuals with chronic conditions and disabilities during the pandemic has been shown in recent literature [31,32], with research showing a negative impact on health and psychological wellbeing of people with disabilities due to isolation based on lack of employment [33]. Study findings showed significant direct effects of anxiety, perceived barriers to employment on work readiness of individuals with NF1 (compared to the control group), and while quality of life were significant indirect effects.…”
Section: Vocational Rehabilitation As An Interventionmentioning
confidence: 78%
“…especially as it relates to incidences and severity of depression and anxiety [3,4]. Furthermore, concerns regarding job loss among individuals with chronic conditions and disabilities [5][6][7] and isolation due to lack of employment has had a negative impact on health and psychological well-being [8].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PWD faced "barriers and concerns during the COVID-19 pandemic as a result of longstanding and pervasive systemic ableism that places them at risk for additional stress and trauma" (Lund et al, 2020, p. 319). These mental health concerns included increased anxiety and depression (Nieweglowski & Sheehan, 2021;Wang et al, 2022), increased substance use (Rumrill et al, 2021), and worsened health outcomes because of increased social isolation and loneliness (Luchetti et al, 2020;Rumrill et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, research has demonstrated that no discrepancy in employment experience was observed between Hispanics and Whites with disabilities, and that acculturation plays a role in positive employment experiences in Hispanic with disabilities (Rumrill et al, 2021;Velcoff et al, 2010). Rumrill et al (2021) found that Hispanics with multiple sclerosis (MS) were equally satisfied with their employment situation as Whites with MS.…”
Section: Employment Experiences Of Hispanics With Disabilitiesmentioning
confidence: 99%
“…In contrast, research has demonstrated that no discrepancy in employment experience was observed between Hispanics and Whites with disabilities, and that acculturation plays a role in positive employment experiences in Hispanic with disabilities (Rumrill et al, 2021;Velcoff et al, 2010). Rumrill et al (2021) found that Hispanics with multiple sclerosis (MS) were equally satisfied with their employment situation as Whites with MS. Compared to the matchedcomparison group of Whites, Hispanics were more satisfied with their legal rights (e.g., knowledge of their employment rights, rights, disability benefits programs) and personalenvironmental resources (e.g., family-oriented culture).…”
Section: Employment Experiences Of Hispanics With Disabilitiesmentioning
confidence: 99%